Odnos med kratkim presejalnim preizkusom spoznavnih sposobnosti in izidom rehabilitacije po amputaciji spodnjega uda - Rutar, Miha (Rehabilitacija (Ljubljana), 2023)
Background: Fitting of prosthesis after lower limb amputation (LLA) requires not only physical, but also cognitive capacity. Hence, we wanted to evaluate how Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) are associated with rehabilitation outcomes in patients after lower-limb amputation. Methods: Data from 155 patients (119 men; median age 69 years) after lower-limb amputation who had completed inpatient rehabilitation at the University Rehabilitation Institute in Ljubljana between September 2017 and February 2018 were analysed. Until January 2018, they were cognitively tested with MMSE (n=66), afterwards with MoCA (n=89). Primary study outcome was prosthesis fitting; secondary outcomes were ability to independently don the prosthesis, ability to independently climb stairs using the prosthesis, walking aid type and 6-minute-walk-test. Propensity-score-matching and regression models with matching variables as additional covariates were applied to adjust parameter estimates for group-imbalance. We also assessed how cognitive impairment cut-off agrees with the outcomes within each group. Results: Regression models showed no statistically significant difference between the groups regarding association with the outcomes. MMSE/MoCA score was statistically significantly positively associated with prosthesis fitting and result of 6-minute-walk-test. Observed agreement of cognitive impairment based on MMSE/MoCA score cut-off with prosthesis fitting was higher in MMSE group; agreement with independent prosthesis donning and climbing stairs was higher in MoCA group. A ceiling effect was observed with MMSE scores. Conclusion: When adjusted for relevant patient characteristics, both MMSE and MoCA proved useful for predicting rehabilitation outcomes in patients after lower limb amputation.
Keywords: amputacija; amputation; Amputation, Surgical; cognitive assessment; izid rehabilitacije; Lower Extremity; lower limb; ocenjevanje spoznavnih sposobnosti; opremljanje s protezo; prosthesis fitting; rehabilitation; rehabilitation outcome; spodnji ud